Comparison of Service Quality and Satisfaction with Parcel Delivery Companies in Thailand on Generation Y Customers - Monphetch, Nuttaphol (Journal of Human and Society, Sisaket Rajabhat University, 2022)
The purposes of the research “comparison of service quality and satisfaction with parcel delivery companies in Thailand on generation Y customers” was to compare the service quality and satisfaction of parcel delivery companies in Thailand on generation Y customers. This study was carried out on a sample of 400 customers between the age of 22-37 years old who have been customers of 3 private parcel delivery companies (Kerry Express, Flash Express, and J&T Express) via questionnaires. The data from online questionnaires was analysed into descriptive statistics. The frequency, percentage, mean, standard deviation and hypothesis testing. were used to analyze the data. The research found that most of respondents were female and unmarried that between the age of 29-32 years old. Most of them graduated with bachelor’s degree. They were employees in private companies and the average monthly income around 20,001-30,000 baht. The frequency of using parcel delivery service were 2-3 times per month. Factors that affect in choosing the service were convenience (branch close to your residence or office). Kerry Express was the highest average score with service quality and satisfaction with service.